Social beings : - Fiske, Susan T. (J. Wiley, 2010)
Fiske provides psychologists with a cutting-edge approach on evolutionary and cross-cultural psychology. The book addresses research on three different levels: brain function and cognition, individual and situations, and groups and cultures. The second edition has been updated to present contemporary research in social psychology. It also discusses increasingly important issues in the field. This includes emotion science and the impact of neuroscience on social and personality psychology. Psychologists agree that the second edition captures an important movement in social psychology with the core motives approach.